Comparative Efficacy of Certain IPM Strategies Against Tobacco Caterpillar and Head Borer in Sunflower - Dhinda, B.; Nayak, U. S.; Das, C. K.; Panda, S. (International Journal of Bio-resource and Stress Management, 2023)
The Experiments was conducted at Regional Research and Technology Transfer Station, Ranital, Bhadrak, OUAT(Odisha University of Agriculture and Technology), Odisha, India during the summer seasons(Jan-may) of 2019–20 and 2020–21 to evaluate the comparative efficacy some IPM modules against the head borer and leaf eating caterpillar in sunflower. Five IPM modules(three chemo-intensive and two bio-intensive modules) were evaluated against the existing pesticides application-based farmers’ practice. The results revealed that the IPM module (M2) comprising of installation of pheromone traps for pest monitoring @ 5 ha-1, poison baits (10 kg rice bran+2 kg jaggery+100 g Thiodicarb 70WP) for attracting and killing of tobacco caterpillar larvae and alternate spray of neem oil formulations (1500 ppm) @ 1.5 l ha-1 and the novel insecticide mixed formulation (Novaluron 5.25%+Emamectin benzoate 0.9% SC) @ 825 ml ha-1 at 15 days interval had significantly suppressed tobacco caterpillar (5.46% leaf damage i.e.. 67.59% reduction over FP) and sunflower head (2.93% head damage i.e. 75.32% deduction over FP). The IPM module ( M3) comprising of pheromone trap installation @ 5 each ha-1,poison baits (10 kg rice bran+2 kg jaggery+200 ml deltamethrin 5EC) and alternate spray of neem oil formulations (1500 ppm) @ 1.5 l ha-1 and Flubendiamide 480 SC @ 150 ml ha-1) also had statistically similar efficacy against the target pests with 6.40% leaf damage (62.02% reduction over FP) and 3.54% head damage(70.17% reduction over FP). Though, the BIPM module had moderate efficacy against the insect-pests under study, retained maximum population of predatory fauna like predatory bug (Eocanthecona furcellata) and lady bird beetles in the sunflower ecosystem.